The consequences of modernity - Giddens, Anthony (SP, 1990)
In this major theoretical statement, the author offers a new and provocative interpretation of institutional transformations associated with modernity. What is modernity? The author suggests, "As a first approximation, let us simply say the following: 'modernity' refers to modes of social life or organization which emerged in Europe from about the seventeenth century onwards and which subsequently became more or less worldwide in their influence."